Els evangelistes en els vitralls medievals catalans = The Evangelists in Catalan medieval stained-glass windows - Cañellas, Sílvia (Miscel·lània litúrgica catalana, 2024)
The Evangelists and their symbols (tetramorph) appeared in many examples of medieval art, including in stained glass. Specifically, this article looks into the different models of these images in Catalan Gothic stained-glass windows.